2010
DOI: 10.1080/10888430903242043
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Overlap Between SLI and Dyslexia in Chinese: The Role of Phonology and Beyond

Abstract: This study examined the overlap of dyslexia and specific language impairment (SLI) in Cantonese-Chinese-speaking children. Thirty children with a prior diagnosis of SLI and 9 normal controls, aged between 6;0 and 11;3, participated. The children with SLI were tested for language impairment and dyslexia. Seven retained a diagnosis of SLI but were dyslexia-free (SLI-only), 13 received a comorbid diagnosis of dyslexia (SLI-D), and SLI had become history (SLI-H) in the other 10 children with no co-morbid diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 74 publications
4
32
0
Order By: Relevance
“…These results are practically important. They underscore the overlap between language delay and dyslexia found in previous work in Hong Kong (Wong et al, 2010). In addition, they highlight the importance of going beyond phonological sensitivity measures only to diagnose subsequent reading difficulties in Chinese children.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results are practically important. They underscore the overlap between language delay and dyslexia found in previous work in Hong Kong (Wong et al, 2010). In addition, they highlight the importance of going beyond phonological sensitivity measures only to diagnose subsequent reading difficulties in Chinese children.…”
Section: Discussionsupporting
confidence: 80%
“…In Hong Kong, where children generally begin formal instruction in literacy by about the age of 3.5 years, early predictors of dyslexia are particularly important. Wong, Kidd, Ho, and Au (2010) demonstrated that approximately 43% of Hong Kong Chinese children ages 6 to 11 years old with a prior history of early language delays manifested dyslexia, a similar pattern to that found in alphabetic languages. However, that study was retrospective in nature, involving children from a wide‐ranging age group.…”
mentioning
confidence: 63%
“…Furthermore, isolation points of words (especially from low-density neighborhoods) correlate with measures of reading, nonword reading, and phonological awareness (Boada & Pennington, 2006;Bruno et al, 2007;Metsala, 1997b; but see Griffiths & Snowling, 2001). This difficulty extends to children with specific language impairment, who often have severe reading problems (Dollaghan, 1998;Wong, Kidd, Ho, & Au, 2010).…”
Section: The Phonological Representations Hypothesis Of Readingmentioning
confidence: 95%
“…In addition, morphological awareness, syntactic awareness and verbal memory were also found to be core deficits in Chinese dyslexic individuals (Chik et al , ; Chung, Ho, Chan, Tsang, & Lee, ; Shu, McBride‐Chang, Wu, & Liu, ). In particular, Chinese dyslexic children were observed to share with SLI children a broad range of impairments in language and reading‐related cognitive skills including phonological retrieval, memory and awareness, and morphological awareness (Wong, Kidd, Ho, & Au, ). Given the special semantic and syntactic features in Chinese, it can be expected that dyslexic children will face a big challenge to differentiate subtle word meanings and process syntactic word order in reading tasks.…”
Section: Introductionmentioning
confidence: 99%